2008
DOI: 10.1021/jm800735d
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Optimization of a Novel Inhibitor of Mitochondrial Calpain 10

Abstract: Calpain 10 has been localized to the mitochondria and is a key mediator of Ca 2+ induced mitochondrial dysfunction. A peptide screen followed by a series of modifications identified the homodisulfide form of CYGAK (CYGAK) 2 as an inhibitor of calpain 10, while showing no inhibitory activity against calpain 1. Methylation or truncation of the N-terminal cysteine significantly reduced the inhibitory activity of (CYGAK) 2 and inhibition was reversed by reducing agents, suggesting that CYGAK forms a disulfide with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…After being transfected into NIH-3 T3 cells, a calpain 10-green fluorescent protein (GFP) fusion protein was targeted to the mitochondria, and the N-terminal 15 amino acids of calpain 10 were found to be sufficient for mitochondrial targeting (Arrington et al, 2006).Functionally, mitochondrial calpain 10 was implicated in Ca 2+ -induced mitochondrial dysfunction as measured by mitochondrial swelling and decreased mitochondrial respiration, the latter of which was inhibited by calpeptin at submicromolar levels. Multipleproteolytic targets for mitochondrial calpain 10 were identified including NADH dehydrogenase (ubiquinone) flavoprotein 2 (NDUFV2) and NADH dehydrogenase (ubiquinone) 1 beta subunit 8, ORP150 and ATP synthase subunit beta.. To validate the role of mitochondrial calpain 10, our laboratory developed a calpain 10-specific peptide inhibitor with an IC 50 of $100 nM that prevented the Ca 2+ -induced reduction in state 3 respiration and mitochondrial calpain 10 substrate cleavage (Rasbach, 2009).…”
Section: Mitochondrial Calpainsmentioning
confidence: 99%
“…After being transfected into NIH-3 T3 cells, a calpain 10-green fluorescent protein (GFP) fusion protein was targeted to the mitochondria, and the N-terminal 15 amino acids of calpain 10 were found to be sufficient for mitochondrial targeting (Arrington et al, 2006).Functionally, mitochondrial calpain 10 was implicated in Ca 2+ -induced mitochondrial dysfunction as measured by mitochondrial swelling and decreased mitochondrial respiration, the latter of which was inhibited by calpeptin at submicromolar levels. Multipleproteolytic targets for mitochondrial calpain 10 were identified including NADH dehydrogenase (ubiquinone) flavoprotein 2 (NDUFV2) and NADH dehydrogenase (ubiquinone) 1 beta subunit 8, ORP150 and ATP synthase subunit beta.. To validate the role of mitochondrial calpain 10, our laboratory developed a calpain 10-specific peptide inhibitor with an IC 50 of $100 nM that prevented the Ca 2+ -induced reduction in state 3 respiration and mitochondrial calpain 10 substrate cleavage (Rasbach, 2009).…”
Section: Mitochondrial Calpainsmentioning
confidence: 99%
“…The percentage inhibition was approximately 20% of the AngII-elicited maximal response, a slightly lower degree of inhibition than was observed with the pan-calpain inhibitors, although we were somewhat limited in the dosage of CYGAK that we could test as this newly synthesized inhibitor is not commercially available (28,32). Nevertheless, this result provided evidence for a role of calpain-10 in AngII-elicited aldosterone production, although potential roles for other atypical calpains are not excluded.…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, the equipotency of CYGAK and CYGAK-OC in mitochondrial matrix is likely the result of cleavage of the oleic acid prior to inhibition. We have previously shown that CYGAK does not inhibit calpain 1, 22 providing evidence that CYGAK is specific for calpain 10. Therefore, we determined the effects of CYGAK, CYGAK-OC, and CYGAK-ON in isolated cytosol, where calpains 1, 2, and 10 are available.…”
Section: Resultsmentioning
confidence: 93%
“…Previously we showed that CYGAK monomers quickly form homodimers in solution, and all experiments are the result of homodimer exposure. 22 Additionally, we have shown that a heterodimer ( i.e. , MeOPh-CYGAK) is a more potent calpain inhibitor than CYGAK, and thus use of a heterodimer should not greatly impact inhibition.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation